2022
DOI: 10.1111/luts.12425
|View full text |Cite
|
Sign up to set email alerts
|

Men suffering from category III chronic prostatitis may benefit from N‐acetylcysteine as an adjunct to alpha‐blockers

Abstract: Objective: We designed this study to investigate the potential use of N-acetylcysteine (NAC) as an adjunct to alpha-blockers in the treatment of category III chronic prostatitis (CP).Methods: Sixty-three men with category III CP with a National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) total score of 15 or more were randomized to either the NAC treatment group or the placebo treatment group. Besides tamsulosin at a dose of 0.4 mg once daily, participants based on their allocation group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…We followed three glass test as this yielded good result and was cost effective. According to Yaryari AM et.al N N-acetylcysteine treatment bene ts men with category III CP [13]. Diclofenac Na was well tolerated by 88.7% of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…We followed three glass test as this yielded good result and was cost effective. According to Yaryari AM et.al N N-acetylcysteine treatment bene ts men with category III CP [13]. Diclofenac Na was well tolerated by 88.7% of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, patients with CP/CPPS can be treated with low-dose daily antibiotics, alpha-1 antagonists, 5-alpha reductase inhibitors, anti-inflammatory agents, phytotherapy and neuromodulatory agents. N-acetylcysteine could be useful as an adjunct to alpha-blockers, too [ 32 ]. Nevertheless, a recent review highlighted how pharmacological treatments had little evidence supporting their efficacy in CP/CPPS [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…
In both diseases, there is a chronic inflammatory process in which pro-inflammatory cytokines and oxygen and nitrogen reactive species (ROS/RNS) play an important role (6-10). Furthermore, there are studies in the literature that have confirmed the therapeutic efficacy of the use of antioxidant substances in both diseases (10)(11)(12)(13)(14)(15). We also know that pro-inflammatory cytokines, Tumor Necrosis Factor (TNF), and interleukin 1 and 6 (IL-1 and IL-6) are present at high levels in the inflammatory process of PD and chronic prostatitis (CP) (6, 7).
…”
mentioning
confidence: 99%